Factors Influencing the Effectiveness of Group Contribution in Student Businesses - Sentosa, Gwyneth Rachel; Djunaidy, Angelina Jocelyn; Kellen, Liong; Mustikarini, Carolina Novi (International Business Management - Universitas Ciputra, 2025)
This research aims to determine the factors that influence the effectiveness of group contributions in student businesses carried out in groups at STIE Ciputra Makassar, which implements an entrepreneurship-based curriculum to support students in developing their businesses. This study focuses on identifying four key factors that influence group effectiveness: Effort, Initiative, Responsibility, and Backup Behavior, especially in the context of courses requiring students to create and manage a Start-Up Business. The method and scope of this research involved using Confirmatory Factor Analysis (CFA) to analyze the influence of these four factors on group contribution effectiveness, with data collected from 100 respondents who are students actively involved in group business projects. The results of this study show that all four factors significantly affect the effectiveness of group contributions. Still, the most influential factor is Backup Behavior, as it reflects the importance of having group members who are reliable and willing to help each other to ensure the smooth operation and success of their joint business.